Pertumbuhan dan Hasil Tanaman Kakao (Theobroma cacao L.) Terhadap Pemupukan Pada Lahan Tropika Basah: Growth and Yeild Cocoa Plants (Theobroma cacao L.) of Fertilizer on Wet Tropical Land - Yetti Elidar; Purwati Purwati (Agrifarm : Jurnal Ilmu Pertanian, 2022)
The purpose of this research was to determine the growth and yield of cocoa plants on fertilization on wet tropical land. The research was located on the land of Badak Mekar Village, Muara Badak District, Kutai Kartanegara Regency, East Kalimantan in 2016-2019.The research method was a randomized block design (RBD) with 4 repetitions. Phase I research: factorial experiment with NPK Phonska fertilizer (N) included 3 levels: n0 = 0 kg plant-1); n1 = 0.25 kg plant-1; n2 = 0.5 kg plant-1 and goat manure (k) included 3 levels: k0 = 0 kg plant-1; k1 = 2.5 kg plant-1; k2 = 5.0 kg plant-1. Phase II research: factorial experiment with SP-36 fertilizer (p) included 3 levels: p0 = 0 kg plant-1; p1 = 0.25 kg plant-1; p2 = 0.5 kg plant-1 and KCl fertilizer (k) included 3 levels: k0 = 0 kg plant-1; k1 = 0.25 kg plant-1; k2 = 0.5 kg plant-1. Phase III research: factorial experiment with SP-36 fertilizer (p) included 3 levels: p0 = 0 kg plant-1; p1 = 0.4 kg plant-1; p2 = 0.8 kg plant-1 and goat manure (k) included 3 levels: k0 = 0 kg plant-1; k1 = 7.5 kg plant-1; k2 = 15 kg plant-1. Observation variable phase I research : increase in plant height at 6 months and 18 months after treatment (bsp), increase in stem diameter at 6 and 18 bsp, increase in number of leaves at 6 months of age and yield of cocoa pods. Observation variable phase II research: plant height increase at 3 bsp and 6 bsp, stem circumference at 3 bsp and 6 bsp, yield of cocoa pods, pest and disease attack intensity on cocoa pods. Observation variable phase III research: 1) yield of cocoa pods 2) pest and disease attack intensity on cocoa pods 3) analysis of soil chemical properties: pH, C-organic, N, P, K, alkaline cations, acid cations, cation exchange capacity and base saturation, 4) analysis soil microbes. Data analysis with variance and if significantly different will be Tested for Least Significant Difference (LSD) at the 5% level. Analysis of soil chemical characteristics with the criteria of soil chemical properties Bogor Soil Research Center (PPT) 1983. The results of phase I research: the NPK Phonska fertilizer treatment was very significantly different in the height increase of plants aged 6 bsp and 18 bsp, the increase in the number of leaves aged 6 bsp. The best dose of NPK Phonska fertilization is 0.5 kg of plant-1 (n2). The results of phase II research: the SP-36 fertilizer treatment was very significantly different for all observation variables. The best dose for SP-36 fertilization is 0.5 kg plant-1 (p2). Intensity of pest attack with light damage category and intensity of disease attack with medium damage category on cocoa pods. The results of phase III research: the treatment of SP-36 fertilizer, goat manure and combination of SP-36 fertilizer and goat manure had no significant difference in yield of cocoa pod. The intensity of pest attacks included moderate damage and the intensity of disease attacks included light damage to cocoa pods. The results of the analysis of soil chemical properties were acid soil pH, moderate organic C content, high C/N ratio, low N content, low P content and high K content. The results of soil microbial analysis identified Azotobacteraceae bacteria and Trichoderma fungi.